“Hazardous to health?” Sugar mills and river pollution in Natal, 1869–1901 (Historia, 2021)
Waste from sugar mills and distilleries deposited in streams and rivers in the coastal areas of Natal was the subject of concern and inquiry between 1869 and 1901. The absence of latrines for indentured labourers housed on sugar estates meant the addition of faecal pollution to streams and rivers. Successive legislative attempts to address the issue were defeated through the opposition and influence of those in the sugar industry, labelled the “sugarocracy” by an earlier researcher. Although theWragg Commission of inquiry into Indian immigration advocated specific measures to deal with the pollution of streams and rivers, its findings were ignored. One of the commissioners, James Saunders, a member of the “sugarocracy”, submitted aminority report in which he disputed the contention that the quality of water in rivers and streams was “hazardous to health”. Besides, Saunders’s standpoint, the absence of a major epidemic as a result of pollution of streams and rivers diminished thecredibility of the claim that those water sources posed a threat to public health.
Keywords: Pollution; sanitation; sugar mills; health; “sugarocracy; Saunders; Campbell